Game Engine Conventions and Games that Challenge them: Subverting Conventions as Metacommentary - Fiadotau, Mikhail (Replay. The Polish Journal of Game Studies, 2017)
Consumer-grade game engines such as Multimedia Fusion and RPG Maker have dramatically extended the reach of digital games as a medium. They have also spawned online communities, where conventions and canons of using these tools have evolved. These partly stem from the functional constraints of the game engines themselves and are institutionalized through manuals, examples, tutorials, and games made with them. However, some members of game engine communities actively seek to challenge these conventions by experimenting with the engines and finding ingenious ways to put them to unexpected uses. Such experiments can be regarded as a form of metacommentary on the engines’ capabilities and limitations. While arguably impractical and inefficient, they enrich the scope of what can be done with the engine and can contribute to its further development.